Pan-cancer analysis of bi-allelic alterations in homologous recombination DNA repair genes. Issue 1 (December 2017) - Riaz, Nadeem; Blecua, Pedro; Lim, Raymond; Shen, Ronglai; Higginson, Daniel; Weinhold, Nils; Norton, Larry; Weigelt, Britta; Powell, Simon; Reis-Filho, Jorge
Abstract BRCA1 and BRCA2 are involved in homologous recombination (HR) DNA repair and are germ-line cancer pre-disposition genes that result in a syndrome of hereditary breast and ovarian cancer (HBOC). Whether germ-line or somatic alterations in these genes or other members of the HR pathway and if mono- or bi-allelic alterations of HR-related genes have a phenotypic impact on other cancers remains to be fully elucidated. Here, we perform a pan-cancer analysis of The Cancer Genome Atlas (TCGA) data set and observe that bi-allelic pathogenic alterations in homologous recombination (HR) DNA repair-related genes are prevalent across many malignancies. These bi-allelic alterations often associate with genomic features of HR deficiency. Further, in ovarian, breast and prostate cancers, bi-allelic alterations are mutually exclusive of each other. The combination of these two properties facilitates reclassification of variants of unknown significance affecting DNA repair genes, and may help personalize HR directed therapies in the clinic. Germline mutations in homologous recombination (HR) DNA repair genes are linked to breast and ovarian cancer. Here, the authors show that mutually exclusive bi-allelic inactivation of HR genes are present in other cancer types and associated with genomic features of HR deficiency, expanding the potential use of HR-directed therapies.